DEEP LEARNING: SEBUAH STRATEGI PEMBELAJARAN INOVATIF DALAM KURIKULUM NASIONAL - Erian Fatria; Eka Apriyanti; Agus Priadi (Jurnal Pendidikan Sultan Agung, 2026)
Improving the quality of 21st century education needs to implement various innovative learning strategies that adapt to the development of the industrial era and digitalization. Deep learning comes as a resolution in answering 21st century learning challenges by integrating the use of technology (ICT), artificial intelligence and big data in the learning process. The purpose of this study is to explain the concept and framework of deep learning and identify learning models that can be applied through this approach. The method used in this study is Literature Review (LR). The study results obtained through this study are that in the context of implementing 21st century education, the deep learning approach can help transform the learning process and learning outcomes of students so that students are especially interested in developing critical thinking, communication, collaboration and creativity skills. It is concluded that the deep learning approach based on joyful learning, mindful learning, and meaningful learning can be considered for use in the context of implementing the National Curriculum but it is suggested that collaboration and training are needed to improve the understanding of teachers or educators to implement these approaches and models in accordance with the objectives of the National Curriculum